TASTE SENSITIVITY VARIATIONS IN DIFFERENT SYSTEMIC DISEASES - Jipu Raluca; Șerban Ionela Lăcrămioara; Hurjui Loredana Liliana; Hurjui Ion; Tărniceriu Claudia Cristina; Statescu Cristian; Mitrea Mihaela; Balcoș Carina; Grădinaru Irina (Romanian Society of Oral Rehabilitation, 2020)
Taste disorders affect the quality of life of a large proportion of patients thus, proper oral examination and identification of the local factors can prevent further complications and can lead to a suitable treatment. The availability of testing for the integrity of taste remains limited. Dentists are often the first clinicians to be presented with complaints about changes in taste so they have to be able to evaluate the type of taste dysfunction and to establish if it has a local cause or it is a symptom of a systemic disease. This review provides a summary of the common causes of taste disorders, problems associated with assessing taste function in a clinical context and the management options available to the dental practitioner. The success of treatment for gustatory dysfunction depends upon the etiology and must be combined with smell disorder. The specific treatment for a diagnosed gustatory dysfunction is reduced, so very often the most important aspect of treatment is teaching the patient to coexist with the disorder.